The Solution of Arabic Teaching: Design of Arabic Teaching for Non-Native Speakers through Creative Ways as An Initial Step to Raises Enthusiasm Learning Arabic - Rizqy Maulana Hakim; Adam Doni Mauladi (International Islamic Schools Alliance, 2018)
The Arab world has an extremely rich culture and history with diverse region geographical in the Arabian Peninsula. The religion of Islam was spread in Arab firstly by the prophet Muhammad SAW and the only language he spoke was Arabian well as Arabic also is the language of the Quran. There are 300 million Arabic speakers in the world and Arabic is the official language in 22 countries. Arabic is also one of the six official languages in the United Nations (UN). Arabic language education is very important, benefits that received from learning Arabic could implement into daily life and any aspects such as understanding the meaning of the Holy Qur’an and very potential to increase good relations in international affairs especially among Indonesia and Arab countries. However, Arabic teaching in non-native speakers' countries has some challenges. We observe that the biggest challenge teaching Arabic in Indonesia is the lack of knowledge among society about the benefit that we can gain from learning Arabic and the educational curriculum has been relying heavily on aspects of memorizing without any effective aspects or understanding of the Arabic lesson, it caused the low level of awareness to learn Arabic. Refer to the research of Jamsuri Muhammad Syamsudin and Mahdi Mas’ud on 30 students of IIUM indicates the biggest challenge to learn Arabic influenced by psychological factors such as desire, motivation, and un-confident. The question then is how to increase Arabic enthusiasts in non-native speakers’ countries and how to improve the educational system to learn Arabic effectively? The serious effort to increasing Arabic enthusiasts and to improve the educational curriculum is through simplification of the Arabic curriculum, as said before that much of the curriculum on Arabic depends on rote teaching methods that can’t truly benefit today. This can be done through creative ways and implement human behavior-based approaches or multiple forms of incentives to raises enthusiasm among non-native speakers to learn Arabic. We propose technology and fun activities that giving out the rewards and without it feels as if a burden to learn Arabic. This approach needs to be developed because the individuals need to be encouraged to do things that will bring benefits much than the act itself. In conclusion, solving the challenge of Arabic teaching is neither easy and improves its educational curriculum is crucial. It is hoped that Arabic teaching will have innovation for its development and overcome its challenges.